THE RELATIONSHIP BETWEEN E-HRM PRACTICES AND ORGANIZATIONAL PERFORMANCE: THE MEDIATING ROLE OF ORGANIZATIONAL AGILITY AND SUSTAINABLE COMPETITIVE ADVANTAGE - Khammadee, Preecha (Asian Administration and Management Review, 2023)
Electronic Human Resource Management (E-HRM) is an act of improving the HRM functions to create dynamic and operational capabilities and contributes greatly on organizational performance. This paper examines the relationship between E-HRM practices, organizational agility, sustainable competitive advantage and organizational performance. We conduct a large scale survey of 317 SMEs in Thailand. Data analysis was performed using Pearson correlation analysis, multiple hierarchical regression techniques and structural equation modelling. Results of the study suggest that organizational agility mediates the influence of E-HRM practices on organizational performance. The study also found that E-HRM practices indirectly through sustainable competitive advantage influences organizational performance. The findings suggest the key organizational agility and sustainable competitive advantage include speed, responsiveness, flexibility, competency, operational effectiveness, relational effectiveness, and strategic effectiveness. Through finding this paper contributes to the emerging literature on E-HRM and has practical implication for organization adapting to achieve organizational performance.